2017
DOI: 10.1136/heartasia-2017-010909
|View full text |Cite
|
Sign up to set email alerts
|

Is white rice consumption a risk for metabolic and cardiovascular outcomes? A systematic review and meta-analysis

Abstract: Higher white rice consumption has not been shown to be associated with increased risk of CHD, stroke and T2DM. However, white rice consumption may be associated with increased risk of MetS in certain populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“… 49 Two other meta-analysis (including 207 556 to 1 777 059 participants and 12 391 to 22 537 events) reported no associations between rice consumption and cardiovascular mortality. 50 51 Muraki et al examined the association between white and brown rice consumption and risk of cardiovascular disease in three US cohorts and reported no association, similar to our findings. 50 One probable reason for a higher risk of cardiovascular disease with higher rice intake was attributed to arsenic content in soil and during irrigation which is probably removed by polishing rice.…”
Section: Discussionsupporting
confidence: 86%
“… 49 Two other meta-analysis (including 207 556 to 1 777 059 participants and 12 391 to 22 537 events) reported no associations between rice consumption and cardiovascular mortality. 50 51 Muraki et al examined the association between white and brown rice consumption and risk of cardiovascular disease in three US cohorts and reported no association, similar to our findings. 50 One probable reason for a higher risk of cardiovascular disease with higher rice intake was attributed to arsenic content in soil and during irrigation which is probably removed by polishing rice.…”
Section: Discussionsupporting
confidence: 86%
“…(2018) reported that germinated coloured rice seems to have more nutritional value and biological activity than germinated non‐coloured rice has. Non‐coloured rice seems to have more negative health effects than coloured rice has, such as related to cardiovascular diseases (Krittanawong et a l ., 2017). Moreover, Prasad et al .…”
Section: Discussionmentioning
confidence: 99%
“…The Korean Genome and Epidemiology Study revealed that the prevalence of MetS was different in men and women with different rice preferences [10]. In Indian and Japan it did not find an association between rice consumption and the prevalence of MetS [9,10,11,13]. The main reason for this result is likely to be that the rice consumption differed between southern China and northern China.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have focused on the relationship between cereal consumption and the prevalence of MetS. The literature on rice intake is mixed, with some studies finding a positive relationship [7,8], some no relationship [9,10,11,12,13], and some an inverse relationship [14,15]. In the Japanese population, whole-wheat consumption has been shown to significantly reduce visceral fat obesity, and therefore reduce the risk of MetS [16], but udon noodle consumption was shown to increase the risk of MetS and abdominal obesity [15].…”
Section: Introductionmentioning
confidence: 99%